Assessment and analysis of efficiency system management by innovative factors for sustainable development of national economy from the position satisfaction of vital interests population in Ukraine (Economics and region, 2019)
The scientific and methodological approach to the evaluation and analysis of the efficiency of system management by innovation factors for sustainable development of national economy from the point of view satisfaction vital interest’s population is developed.This is the calculation of the modernized index human development based on the adjective model based on 26 indicators (social, economic and environmental subsystems), as well as using the methods of the main components and the slip matrix. The resultant value is the modernized Human Development Index (MHDІ) of Ukraine.The architectonics MHDІ of Ukraine in 2007–2017 from the position of sub-indices of the ecological, social and economic subsystems is analyzed.Consequently, the scientific and methodological approach based on the MHDI change allows us to draw conclusions regarding the effectiveness of the work and public administration bodies in the context of making managerial decisions regarding the satisfaction of the vital interest’s population. MHDI considers the main regulated parameter of the system management in the innovation factors of sustainable development in socially oriented economy. The tendency of steady decline MHDI of Ukraine in 2007–2017 on 53.45 % was confirmed, which confirms inefficient state regulation of crisis situations in Ukraine.In order to increase the efficiency management of innovative factors by sustainable development of the national economy, from the standpoint of satisfaction vital interest’s population, it is proposed to intensify the use of public debt and savings bonds, market and non-market methods of relief and debt load. This is due to the fact that at the current stage of development in the national economy, public external debt is one of the most significant indicators of the state economy. It is at the same time a criterion for the effectiveness of public financial policy, as well as a threat and opportunity for the Ukrainian economy. In order to optimize its size, various methods, approaches, tools are used. Based on the analysis of world experience, it has been established that the securities market, in particular debt securities, plays a strategic role in regulating this issue. Therefore, it makes sense to recommend government debt bonds and government savings bonds to optimize the amount of external public debt.
Keywords: innovative factors; socio-economic development; national economy; modernized Human Development Index; management